Multi Units of Three Phase Photovoltaic using Band Pass Filter to Enhance Power Quality in Distribution Network under Variable Temperature and Solar Irradiance Level - Adiananda Adiananda; Agus Kiswantono; Amirullah Amirullah (Institute of Advanced Engineering and Science, 2018)
The paper proposed power quality enhancement on three phase grid of point common coupling (PCC) bus due to integration of multi units of photovoltaic (PV) to 380 volt (phase-phase) 50 Hz low voltage distribution network under variable temperature and irradiance level. The band pass filter models (single tuned and double tuned) were installed to improvement power quality on the conditions i.e. without filter, with single tuned filter, and with double tuned filter. Multi units of PV generator without filter, with single tuned, and with double tuned filter at all temperatures and irradiance levels resulted in relatively stable phase voltage (308 and 310 volt), so able to generate an unbalanced voltage of 0%. The maximum phase current for the system without filter at all temperatures and radiation levels of 9.8, 12.5, and 10 ampere respectively, resulted in an unbalanced current of 16.10% . Under the same condition, single tuned and double tuned filters were able to balance phase current to 10.45 A and 10.44 ampere respectively, resulting in an unbalanced current of 0%. Implementation of single tuned and double tuned filters was able to reduce unbalance current according to ANSI/IEEE 241-1990. At constant temperature and irradiance increased, both average voltage and current harmonics also increased. Double tuned active filter was the most effective to suppress the 11th and 13th harmonics so that capable to migitate average voltage and current harmonics better than system using single tuned filter which could only reduce 5th harmonic within IEEE 519-1992.